Can We "Regain" Truth and Objectivity? A Reply to Baillie and Meckler. (April 2014) - Ryan, Phil
James Baillie and Mark Meckler's (B&M) "Truth and Objectivity Regained" misconstrues the author's previous argument. More surprisingly, they also fail to distinguish their own earlier arguments from their current views. This Reply seeks to clear up the confusion. It challenges B&M's claims concerning the "function" of beliefs and statements, and defends the view that objectivity is a matter of degree, depending upon the reasonableness of a statement's background conditions.